Effect of Seed Maturity and Storage Duration on Germination of Sambiloto (Andrographis paniculata) - Solikin, Solikin; Nurfadilah, Siti (Biosaintifika: Journal of Biology & Biology Education, 2017)
Seed maturity and its storage are one of problems on propagation and developing of medicinal plants such as sambiloto (Andrographis paniculata (Burm.f.) ex Nees). The research aimed to determine effects of seed maturity and storage duration on seed germination of sambiloto was conducted in a green house of Purwodadi Botanical Garden from November 2014 to November 2015. The experiment was done by completely randomised design with two treatments namely seed maturity and storage duration. The seed was classified into immature seed (0.061 g/100 seeds), semimature seed (0.113 g/100 seeds) and mature seed (0.166 g/100 seeds). The seeds storage duration was classified into seed was not stored, seed was stored for six months and seed was stored for twelve months. Each treatment combination was replicated five times. The results showed that there were significant interactions between the treatments on percentage and rate of seed germination. The highest percentage of seed germination was the treatment of mature seed and stored twelve months (98.50%). On the contrast, the lowest seed germination percentage was the treatment of immature seed and stored twelve months (4.25 %). The fastest seed germination rate was the treatment of mature seed and stored six months (3.88 days), whereas the slowest seed germination rate was the treatment of immature seed and without stored (28.58 days). This study is expected to be applied to improve genetic and cultivation of medicinal plant as well as increasing plant growth and yield.